182k views
3 votes
11x+7=6x-3
Solve for x.

User Yitsushi
by
5.2k points

2 Answers

4 votes

Answer:

  • X = - 2

Explanation:

We have been given an expression, 11x+7=6x-3.

Step: Add or move the like terms.

  • 11x + 7 = 6x - 3
  • 11x - 6x + 7 + 3 = 0

Step: Solve the parts separately.

  • 5x + 10 = 0
  • 5x = - 10

Step: Divide the expression by 5.

  • 5x/5 = -10/5
  • x = - 2

Therefore, the required value of x is -2.

User David Berg
by
4.6k points
2 votes

11x+7=6x-3

move 6x to the other side

sign changes from +6x to -6x

11x-6x+7= 6x-6x-3 ( combine like terms)

11x-6x+7= -3

5x+7= -3

move +7 to the other side

sign changes from +7 to -7

5x+7-7= -3-7

5x=-3-7

5x=-10

divide both sides by 5 to get x by itself

5x/5= -10/5

answer:

x= -2

User MHS
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.